Adsorption Kinetics and Equilibrium Studies of Reactive Red 198 Dye by Cuttlefish Bone Powder - Mahboobeh Dehvari; Mohammad Hassan Ehrampoush; Mohammad Ghaneian; Behzad Jamshidi; Masoumeh Tabatabaee (Iranian Journal of Chemistry & Chemical Engineering, 2017)
In this research, the removal of Reactive Red 198 dye (RR-198) by Cuttlefish bone powder was investigated. The adsorbent was prepared in laboratory conditions and ground by ASTM standard sieves (60-100 mesh). The progress of the process is monitored spectrophotometrically by measuring the absorbance of dye at 518 nm wavelength. In addition, the effects of process parameters such as adsorbent dose, pH, initial dye concentration, and contact time have been investigated. The SEM micrographs and the XRD pattern showed that the cuttleﬁsh bone has the clearly seen pores on its surface and a crystallized form. According to the results, by increasing adsorbent dose and retention time, dye removal efficiency was increased considerably.The adsorption isotherm for initial dye concentration (50 mg/L) was in good concordance with the Langmuir and Freundlich models. The adsorption kinetic studies revealed that the adsorption of RR198 dye complied with pseudo-second-order kinetic.